Kajian Analitis Kebutuhan Bahan Bakar Gas Insinerator Limbah Medis Dual Chamber Dengan Variasi Temperatur Pada Chamber Kedua - Pujanu Ary Shantika, I Made; Suprapta Winaya, I Nyoman; Arya Darma, I Wayan; Angga Yuda Pratama, I Putu (Teknik Desain Mekanika, 2023)
Abstractt This research was conducted to determine the gas fuel consumption rate of a dual chamber fixed grate medical waste incinerator by varying the combustion temperature in the second combustion chamber, which has been predetermined and can have a direct effect on medical waste treatment. Each sample of medical waste used weighed 1 kg and consisted of masks, infusion bags, syringes, latex, and gauze. The incineration process was carried out at a temperature of 800? C in the first combustion chamber, with a burning duration of 3 minutes and an oxygen flow rate of 23.07 liters/minute. The testing was performed four times with sequential variations of combustion temperatures in the second combustion chamber: 950? C, 1000? C, 1050? C, and 1100? C. The research results showed that the highest gas fuel consumption rate occurred in the fourth variation, amounting to 7.33 kg/hour. Meanwhile, the lowest gas fuel consumption rate was observed in the first variation, at 6.15 kg/hour. Keywords: Fix Grate Dual Chamber Incinerator, Temperature, Second Combustion Chamber, Performance, Fuel Consumption Rate